PLASTICITY OF THE PSYCHROPHILIC GREEN ALGA CHLAMYDOMONAS RAUDENSIS (UWO 241) (CHLOROPHYTA) TO SUPRAOPTIMAL TEMPERATURE STRESS(1) - Possmayer, Marc (Journal of phycology, 2011)
© 2011 Phycological Society of America.